Penerapan Model Pembelajaran Problem Based Learning (PBL) dan Media Komik Strip untuk meningkatkan Keterampilan Menulis Teks Anekdot Kelas X Multimedia SMK Cendekia Madiun Tahun Pelajaran 2023/2024 - Astuti, Harning Diah Juni; Suharto, V. Teguh; Hadi, Panji Kuncoro (Wewarah: Jurnal Pendidikan Multidisipliner, 2024)
This study aims to identify and describe the implementation of teaching and the enhancement of anecdotal text writing activities using the Problem-Based Learning (PBL) model and comic strip media. The type of research used is Classroom Action Research, conducted in two stages: Cycle I and Cycle II. Data collection techniques included tests and non-tests. The test technique consisted of the results of anecdotal text writing skills tests, while the non-test technique included student activity data obtained from observations, interviews, and photo documentation. This research employed qualitative and quantitative data analysis techniques. The results of this study indicate that the implementation of the Problem-Based Learning (PBL) model and comic strip media can improve anecdotal text writing skills. This improvement is evidenced by the average score achieved by students in Cycle I, which was 70.0 (sufficient), while in Cycle II, the average score increased to 81.0 (good). The increase from Cycle I to Cycle II was 10.9 points or 13.5%. Additionally, student activity also showed an improvement in a positive direction. Students were active in the learning process from the beginning to reflection. They were more enthusiastic, motivated, and earnest when participating in learning anecdotal text writing.